1991
DOI: 10.1016/0014-5793(91)80887-9
|View full text |Cite
|
Sign up to set email alerts
|

The formation of 3α‐ and 3β‐acetoxytropanes byDatura stramonium transformed root cultures involves two acetyl‐CoA‐dependent acyltransferases

Abstract: Tropine (tropan-3~-ol) is an intermediate in the formation of hyoscyamine. An acyltransferase activity that can acetylate tropine using acetylcoenzyme A as cosubstrate has been found in translbrmed root cultures of Datura sfr(mtonit#n. A further acyltransferase activity that acetylates pseudotropine (tropan-3fl-ol) with acetyl-coeuzyme A is also present. These two activities can be partially resolved by anion-exchange chromatography, some fractions containing only the pseudotropine-utilizing activity. The basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Although no enzymatic activity had been described, it is likely that an enzyme related to the cocaine synthase may be involved [59,60] in the formation of littorine. Littorine is rearranged via the littorine mutase/monooxygenase (CYP80F1; EC 1.6.2.4) to hyoscyamine aldehyde, which is subsequently reduced to the corresponding alcohol hyoscyamine [61].…”
Section: Ta Biosynthesis In Plantamentioning
confidence: 99%
“…Although no enzymatic activity had been described, it is likely that an enzyme related to the cocaine synthase may be involved [59,60] in the formation of littorine. Littorine is rearranged via the littorine mutase/monooxygenase (CYP80F1; EC 1.6.2.4) to hyoscyamine aldehyde, which is subsequently reduced to the corresponding alcohol hyoscyamine [61].…”
Section: Ta Biosynthesis In Plantamentioning
confidence: 99%
“…Robins [ 102 ] reported that different Datura acyltransferases act depending on whether the substrate is α- 10 or β- 10 . Individual acyltransferases also may have promiscuous substrate specificity.…”
Section: Alkaloids Of the Genus Datura —Tropane Alkaloidsmentioning
confidence: 99%
“…Individual acyltransferases also may have promiscuous substrate specificity. For example, tigloyl pseudotropine acyltransferase isolated from D. stramonium root cultures has the highest activity with tigloyl-CoA, but can also use acetyl, propionyl, isobutyroyl, and senecioyl-CoAs (among other aliphatic substrates) to acylate β- 10 , suggesting that the abundance of a given acyltropane may in part arise from competition between different substrates in the plant’s acyl-CoA (or other acyl donor) pool [ 102 , 103 ]. The aliphatic CoAs utilized by these enzymes are derived from short-chain (C 2 -C 5 ) carboxylic acids.…”
Section: Alkaloids Of the Genus Datura —Tropane Alkaloidsmentioning
confidence: 99%
“…Nevertheless, recent work challenges this long-standing speculation and propose the following roadmap: 3 β -Tropanol is esterified into 3 β -tigloyloxytropane (the key intermediate for the biosynthesis of calystegines), which undergoes demethylation and hydroxylation, followed by hydrolytic reactions, resulting in the production of calystegines 26 . Although Robins and colleagues reported that catalytic activities associated with 3 β -tropanol esterification occurred in Datura stramonium and A. belladonna in the 1990s 27 , 28 , the genes that encode acyltransferases responsible for the formation of 3 β -tropanol esters remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%